2009
DOI: 10.1007/s11814-009-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct preparation of dichloropropanol from glycerol and hydrochloric acid gas in a solvent-free batch reactor: Effect of experimental conditions

Abstract: Solvent-free direct preparation of dichloropropanol (DCP) from glycerol and hydrochloric acid gas was carried out in a batch reactor with a variation of reaction conditions (agitation speed, reaction time, reaction temperature, and reaction pressure), amount of H 3 PW 12 O 40 catalyst, and amount of water absorbent (silica gel blue). The reaction was conducted at high agitation speed in order to avoid mass transfer limitation between glycerol and hydrochloric acid gas. In the direct preparation of DCP from gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…It was found that water formed during the reaction had a negative effect on Downloaded by [Princeton University] at 04:47 17 September 2013 the formation of dichloropropanol. In this aspect, Song et al discovered that in situ absorption of water by an absorbent (e.g., silica gel) during the reaction enhanced the yield of dichloropropanol (395). Particularly, a combination of gaseous hydrogen chloride, heteropolyacid catalyst, absorbent, and silica gel resulted in the significant enhancement of dichloropropanol formation (389).…”
Section: Catalytic Chlorination Of Glycerol To Dichloropropanolmentioning
confidence: 99%
“…It was found that water formed during the reaction had a negative effect on Downloaded by [Princeton University] at 04:47 17 September 2013 the formation of dichloropropanol. In this aspect, Song et al discovered that in situ absorption of water by an absorbent (e.g., silica gel) during the reaction enhanced the yield of dichloropropanol (395). Particularly, a combination of gaseous hydrogen chloride, heteropolyacid catalyst, absorbent, and silica gel resulted in the significant enhancement of dichloropropanol formation (389).…”
Section: Catalytic Chlorination Of Glycerol To Dichloropropanolmentioning
confidence: 99%
“…PG is an important chemical used to make unsaturated polyester resins, functional fluids (antifreeze, de-icing, and heat transfer), personal care, paints, animal feed, food industry coolants, non-ionic detergents, pharmaceuticals, cosmetics, flavours and fragrances, plasticisers and hydraulic brake fluids [107,109]. It is also an excellent solvent and extractant, and used as a tobacco humectant.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 6 (2)mentioning
confidence: 99%
“…To remove the unwanted glycerol from the wanted biodiesel, glycerol may also be used as a reactant in a chemical reaction for the production of dichloropropanol. The reaction is conducted at high agitation speed in order to avoid mass transfer limitation between glycerol and hydrochloric acid gas (Song et al, 2009). To remove the unwanted side products (e.g.…”
Section: Downstream Processingmentioning
confidence: 99%